2016
DOI: 10.1016/j.biocontrol.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, efficiency, and physical characteristics of predation by generalist predators of brown marmorated stink bug (Hemiptera: Pentatomidae) eggs

Abstract: Morrison et al.; Frequency, feeding habits … Submitted to: Biological Control 1 2 Frequency, efficiency, and physical characteristics of predation by generalist predators 3 of brown marmorated stink bug (Hemiptera: Pentatomidae) eggs 4 5 2 Morrison et al.; Frequency, feeding habits … Abstract 15The native generalist predator community of Halyomorpha halys, an invasive species in the 16 United States and Europe, has not been well defined to date. The aims of the current study 17 were to determine whether genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 42 publications
5
69
1
1
Order By: Relevance
“…In the United States, predation on sentinel egg masses was similarly low, ranging from 4% to 11% (Cornelius et al, ; Jones et al, ; Ogburn et al, ). In these surveys, tettigonids and carabids were identified as the most efficient predators of H. halys eggs (Morrison et al, ). In our survey, we observed residues of eggshells, possibly preyed by chewing predators, but their identity remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the United States, predation on sentinel egg masses was similarly low, ranging from 4% to 11% (Cornelius et al, ; Jones et al, ; Ogburn et al, ). In these surveys, tettigonids and carabids were identified as the most efficient predators of H. halys eggs (Morrison et al, ). In our survey, we observed residues of eggshells, possibly preyed by chewing predators, but their identity remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although fresh food was provided to the caged adults twice a week, cannibalism might have occurred to respond to physiological necessity of alternative, protein‐rich food sources (Thomas & Manica, ). Apart from cannibalism, eggs could have been eaten by predators with piercing–sucking mouthparts, small enough to penetrate the mesh barrier, such as Miridae and Anthocoridae, that have been reported as predators of H. halys eggs in previous studies (Abram et al, ; Morrison et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though we have employed the most efficacious compounds against H. halys , we were unable to eliminate the threat posed by H. halys , as adults remained mobile after brief exposure to field recommended rates. Further research should evaluate any sublethal effects that may affect recently identified generalist natural enemies or parasitoids of H. halys . In addition, a larger selection of insecticides (including those that are less effective) should be assessed for the effects of brief exposures on the mobility and behavior of H. halys , as well as investigating additional measures such as the consequences that brief doses may have on the fecundity and development of earlier developmental stages.…”
Section: Discussionmentioning
confidence: 99%